2007
DOI: 10.1073/pnas.0702609104
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic engineering of Escherichia coli for the production of l -valine based on transcriptome analysis and in silico gene knockout simulation

Abstract: The L-valine production strain of Escherichia coli was constructed by rational metabolic engineering and stepwise improvement based on transcriptome analysis and gene knockout simulation of the in silico genome-scale metabolic network. Feedback inhibition of acetohydroxy acid synthase isoenzyme III by L-valine was removed by site-directed mutagenesis, and the native promoter containing the transcriptional attenuator leader regions of the ilvGMEDA and ilvBN operon was replaced with the tac promoter. The ilvA, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
306
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 501 publications
(318 citation statements)
references
References 36 publications
1
306
0
1
Order By: Relevance
“…At the same time, endogenous pathways can be shut down or reduced [80] to optimize the balance between heterologous and endogenous biochemical activities [79]. Side effects or roadblocks encountered can be ameliorated or removed by multiple rounds of engineering [79,81,82].…”
Section: / Metabolic Engineeringmentioning
confidence: 99%
“…At the same time, endogenous pathways can be shut down or reduced [80] to optimize the balance between heterologous and endogenous biochemical activities [79]. Side effects or roadblocks encountered can be ameliorated or removed by multiple rounds of engineering [79,81,82].…”
Section: / Metabolic Engineeringmentioning
confidence: 99%
“…Applications of the E. coli GEM range from pragmatic to theoretical studies, and can be classified into five general categories ( Fig. 3): 1) metabolic engineering [20][21][22][23][24][25][26][27][28][29][30] ; 2) biological discovery [31][32][33][34][35][36][37] ; 3) assessment of phenotypic behavior 19, ; 4) biological network analysis [64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79] ; and 5) studies of bacterial evolution [80][81][82] . The in silico methods used to probe the E. coli GEM in each study are summarized in Fig.…”
Section: Ask Not What You Can Do For a Reconstruction But What A Recmentioning
confidence: 99%
“…Through the application of computational methods that incorporate linear, mixed integer linear, and non-linear programming, it has been demonstrated that model-directed strain design can lead to increased metabolite production [20][21][22][23][24][25][26][27][28][29][30] . In these studies, the E. coli GEM is principally used to analyze the metabolite production potential of E. coli and identify metabolic interventions needed to enable the production of the product of interest.…”
Section: Applications Of Gems To Metabolic Engineering Of E Colimentioning
confidence: 99%
See 2 more Smart Citations